Aspectos epidemiológicos e clínicos da paracoccidioidomicose no Estado do Espírito Santo - Peçanha, Paulo Mendes (2012)
In a serie of cases of paracoccidioidomycosis we retrospectively reviewed the records of 546 patients treated at the Hospital Universitario Cassiano Antonio Moraes (HUCAM), Federal University of Espírito Santo - UFES, from 1978 to 2012. The patients ages ranged from 7 to 83 years, with 512 males and 34 females in a ratio of 15:1. Most of the patients( 81,34%) were from the state of Espírito Santo (ES), 18,66% came from other states, mainly from rural areas and 77,6% of them were farmers. The map of geographical distribution in ES showed higher concentration of cases in counties in the western border, along Minas Gerais state.Looking at the clinical features 60 (10.99%) patients presented the acute / subacute form of the disease, 485 (88.83%) the chronic form and one patient the subclinical form. The organs most often affected were the lungs, oropharyngeal mucosa, lymph nodes, skin and larynx. Several other organs were also affected less frequently. The diagnosis was established by histopathology in 252 (46.15%), direct examination in 168 (30.77%), direct examination and histopathology in 111 (20.33%) and serology in 15 (2.75%) patients. The infectious diseases more frequently associated were tuberculosis, AIDS, leishmaniasis and intestinal parasites. Patients were treated with sulfonamides, or azole in mild to moderate forms and amphotericin B in severe forms. The length of the treatment was analysed in 366 patients. Only 146 (40%) completed the minimum of 18 months needed when taking sulphonamides. The most common sequelae were residual pulmonary lesions and scars on skin and mucous membranes. The number of cases in this serie highlights the state of Espírito Santo as important endemic area of paracoccidioidomycosis in Brazil and the results follow the clinical and epidemiological patterns demonstrated in other series.